2008
DOI: 10.1371/journal.pone.0002559
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal Fluid B Cells Correlate with Early Brain Inflammation in Multiple Sclerosis

Abstract: BackgroundThere is accumulating evidence from immunological, pathological and therapeutic studies that B cells are key components in the pathophysiology of multiple sclerosis (MS).Methodology/Principal FindingsIn this prospective study we have for the first time investigated the differences in the inflammatory response between relapsing and progressive MS by comparing cerebrospinal fluid (CSF) cell profiles from patients at the onset of the disease (clinically isolated syndrome, CIS), relapsing-remitting (RR) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
76
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(82 citation statements)
references
References 39 publications
4
76
1
Order By: Relevance
“…Most patients (34 of 39) had OCBs in their CSF, suggesting a preestablished intrathecal plasma cell repertoire as potential evidence for immune activation and CNS infiltration that may have occurred prior to CSF sampling. With regards to the CSF lymphocyte composition, we confirmed that T lymphocytes are much more prevalent than B cells in CSF of MS patients, that absolute numbers of both B and T cells are increased in active MS (27), and that the CSF is enriched with memory B cells (28). In patients with Gd + lesions on brain MRI, we found a disproportionate increase in B cell numbers compared with T cells, suggesting that B cell immigration and/or activation is associated with active MS. We found increased CD27 hi B cells in CSF, confirming earlier reports that intrathecal plasma cells are associated with active CNS inflammation in MS (12,29) and suggesting antigen-driven B cell activation.…”
Section: Discussionmentioning
confidence: 60%
“…Most patients (34 of 39) had OCBs in their CSF, suggesting a preestablished intrathecal plasma cell repertoire as potential evidence for immune activation and CNS infiltration that may have occurred prior to CSF sampling. With regards to the CSF lymphocyte composition, we confirmed that T lymphocytes are much more prevalent than B cells in CSF of MS patients, that absolute numbers of both B and T cells are increased in active MS (27), and that the CSF is enriched with memory B cells (28). In patients with Gd + lesions on brain MRI, we found a disproportionate increase in B cell numbers compared with T cells, suggesting that B cell immigration and/or activation is associated with active MS. We found increased CD27 hi B cells in CSF, confirming earlier reports that intrathecal plasma cells are associated with active CNS inflammation in MS (12,29) and suggesting antigen-driven B cell activation.…”
Section: Discussionmentioning
confidence: 60%
“…However, EBV-infected B cells [35] and EBV cell-free virions [18,36] were rarely observed in the CSF of MS patients. This may be accounted for by the low frequency of B cells present in the CSF [37], the maintenance of virus-specific memory CD8 1 T cells in the absence of cognate antigen [38] or by the specific presence of reservoirs for EBV in other brain compartments [18]. In any case, since the EBV-specific intrathecal immune responses, both humoral and cellular, were increased in our patients with early MS, it is likely that some EBV reactivation has been taking place in their CNS.…”
Section: Discussionmentioning
confidence: 99%
“…However, a diagnostic method should not depend on mere differences in incidence rates. Furthermore, increased levels of CSF-CXCL13 have also been reported in MS, albeit at lower levels, in general, compared with LNB (12)(13)(25)(26)(27). Although CXCL13 in CSF is a more specific marker for LNB compared to pleocytosis, which may be found in many other central nervous system diseases such as bacterial and viral meningitis and various inflammatory central nervous system diseases (13), the increased CXCL13 levels found in MS and NS point to the benefit of combining results of CXCL13 with intrathecally produced anti-borrelia antibodies in order to gain diagnostic specificity.…”
Section: Discussionmentioning
confidence: 99%